Pracownicze programy emerytalne w Polsce - Dybał, Mariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The aging of society, the financial and economic crisis and low interest rates have a strong impact on mature pension systems. This leads to fiscal difficulties in pay-as-you-go public systems. As a result, there is a conflict between income adequacy and financial stability of pension systems. In order to reconcile the adequacy with stability, many countries reform pension systems in areas such as system structure, pension contributions, eligibility criteria, funding methods, management methods, pension benefits, taxation. There is also a question of how to obtain additional funding sources for retirement. It seems that one of the instruments to obtain additional financial resources in old age may be participation in Occupational Pension Schemes (PPE), which in Poland offered their services in 1999 on the basis of the Act of 22 August 1997 on Occupational Pension Plans. Thus, the research objective of the work, which is the analysis of PPE in Poland in the years 1999–2016, is revealed
Keywords: pracownicze programy emerytalne; programy emerytalne; systemy emerytalne